1990
DOI: 10.1128/iai.58.9.2733-2737.1990
|View full text |Cite|
|
Sign up to set email alerts
|

Production of immunoglobulin A protease by Streptococcus pneumoniae from animals

Abstract: Human isolates of Streptococcus pneumoniae tested by traditional immunochemical methods produce a protease that cleaves human immunoglobulin A1 (IgA1) into Fab and Fc fragments. The protease may be an important virulence factor, but studies of its pathogenetic significance have been hampered by lack of a suitable animal model. Since S. pneumoniae is a respiratory pathogen for several species of animals, we sought to determine whether isolates of this organism from animals with pneumococcal infection, including… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

1991
1991
2010
2010

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(18 citation statements)
references
References 21 publications
0
18
0
Order By: Relevance
“…From genomic analysis, we know that our CBP is different from the abovementioned genes that map at other loci on the G54 chromosome. From our in vivo screen, we identified a mutant (SPN-1810) with an insertion in the IgA1 protease; this enzyme belongs to the class of extracellular endopeptidases which specifically cleave human (52) but not mouse (48) IgA1. It has recently been found that in Neisseria gonorrhoeae, IgA1 protease is important for survival of this pathogen within epithelial cells due to its ability to cleave LAMP1, a major integral membrane protein of lysosomes (35).…”
Section: Discussionmentioning
confidence: 99%
“…From genomic analysis, we know that our CBP is different from the abovementioned genes that map at other loci on the G54 chromosome. From our in vivo screen, we identified a mutant (SPN-1810) with an insertion in the IgA1 protease; this enzyme belongs to the class of extracellular endopeptidases which specifically cleave human (52) but not mouse (48) IgA1. It has recently been found that in Neisseria gonorrhoeae, IgA1 protease is important for survival of this pathogen within epithelial cells due to its ability to cleave LAMP1, a major integral membrane protein of lysosomes (35).…”
Section: Discussionmentioning
confidence: 99%
“…The lack of cleavage of IgA of most animals, in contrast to humans, may indeed be a result of the lack of an extended hinge region as in human IgA1. Proctor & Manning (124) and ourselves (58) is that IgAl protease-producing streptococci may be isolated from animal species whose IgA apparently is not susceptible to the protease. Thus, isolates of S. pneumoniae from respiratory infections in mice, rats, dogs, rabbits, and rhesus and cynomolgus monkeys cleaved IgAl of human and gorilla origin, but not IgA of the animals from which the bacteria were isolated (124).…”
Section: Analogous Host-parasite Relationshipsmentioning
confidence: 99%
“…Proctor & Manning (124) and ourselves (58) is that IgAl protease-producing streptococci may be isolated from animal species whose IgA apparently is not susceptible to the protease. Thus, isolates of S. pneumoniae from respiratory infections in mice, rats, dogs, rabbits, and rhesus and cynomolgus monkeys cleaved IgAl of human and gorilla origin, but not IgA of the animals from which the bacteria were isolated (124). The initial finding that IgA from rhesus monkeys was cleaved (124) cannot be reproduced, in full agreement with the absence of a similar hinge region in rhesus monkey IgA (129).…”
Section: Analogous Host-parasite Relationshipsmentioning
confidence: 99%
“…Though cleavage of human IgAl is the only function verified, IgAl proteases may in addition serve other purposes. The association between meningococcal type 1 cleavage and virulence (Lomholt et al, 1992) as well as isolation from animals of bacteria that excrete IgAl protease cleaving human while not host IgA (Kilian & Reinholdt, 1986;Proctor & Manning, 1990), may be suggestive of alternative substrates for all or certain types of the enzyme. In this context, evidence has been presented suggesting that the gonococcal IgAl protease h c t i o n to modifjl outer membrane proteins of the bacterium itself @hoberg & Mulks, 1991).…”
Section: Substrate Specificitymentioning
confidence: 99%